Comparative assessment of plasmid DNA delivery by encapsulation within or adsorbed on poly (D, L-lactide-co-glycolide) nanoparticles - Doolaanea, Abd Almonem; Mansor, Nur 'Izzati; Mohd Nor, Nurul Hafizah; Mohd Shafri, Mohd Affendi; Mohamed, Farahidah (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, Benin City, Nigeria, 2018)
Purpose: To compare the gene delivery effectiveness of plasmid DNA (pDNA) encapsulated within poly (D,L-lactide-co-glycolide) (PLGA) nanoparticles with that adsorbed on PLGA nanoparticles. Methods: PLGA nanoparticles were prepared using solvent-evaporation method. To encapsulate pDNA within the particles, it was first complexed with cetyltrimethylammonium bromide (CTAB) and then added to the oil phase during the synthesis. For the adsorption, PLGA nanoparticles were first modified with either CTAB or chitosan and then pDNA was adsorbed on the particle surface by electrostatic interaction. Results: Nanoparticles encapsulating pDNA exhibited better plasmid loading and protection with significantly lower burst release (p < 0.05) compared to that of the nanoparticles with adsorbed plasmid. Cell uptake of chitosan-modified nanoparticles by murine neuroblastoma (N2a) cells was significantly (p < 0.05) higher than that of chitosan-free nanoparticles. Nanoparticles encapsulating pDNA showed higher transfection efficiency (p < 0.05) in N2a cells. Conclusion: Encapsulation of pDNA within PLGA nanoparticles presents a potential strategy for gene delivery that is superior to pDNA adsorbed on the nanoparticle surface. In addition, encapsulation keeps the particle surface free for further modifications such as the addition of targeting ligands.